Rheological Behaviour and Properties of Injection Moulded Oil Palm (Elaeis Gunineensis Jacq.) Empty Fruit Bunch Fibres/Polyproplene Composites) - Abdan, Khalina (2005)
The feasibility of processing composite prepared from oil palm empty fruit bunch (EFB) /polypropylene (PP) using injection moulding was investigated. The physical! chemical, and thermal characteristics of EFB fibre were studied. The effects of fibre size, fibre content, levels of melt flow rate and various concentration of maleated polypropylene (MAPP) on the mechanical, physical, rheological and thermal properties of EFBIPP composites were studied. The effects of types and concentrations of reactive additives (RA) on the irradiated EFBlPP composites were also investigated especially to the rheological behaviour and dynamic mechanical thermal characteristics. The EFBlPP composites were prepared from thermomechanically pulped EFB fibre and PP resin. The internal mixer was used to mix and the injection moulding machine was employed to form the specimen accordance to the ASTM standards. Electron beam was used to irradiate the EFBIPP composite in order to investigate the effect on dynamic mechanical thermal properties and rheological behaviour. The rheological behaviour was studied using the rheostress viscometer and the results were compared to the melt flow index. Dynamic mechanical thermal properties were measured using a Triton model dynamic mechanical analyser. The EFB fibre size and fibre content significantly affected the mechanical and physical properties of EFBIPP composites. However the effect of type and concentration of MAPP only affected the tensile and shrinkage properties of the moulded composites. The rheology of PP showed pseudoplastic behaviour and the viscosity was constant at low shear rate. The changes in fibre size marked different viscosity condition with fine fibre showed viscosity curve away from the matrix curve particularly at very low shear rate. However the 0.1-0.2 mm fibre size revealed the viscosity trend close to the matrix. When MAPP additives were added in the EFBIPP composites the viscosity curve was changed depending on type and concentration level. 2 % of both types of MAPP produced slightly increase in viscosity but 6% of MAPP dropped down the viscosity. The irradiated EFBIPP significantly decrease the viscosity however the composites treated by trimethylol propane triacrylate (TMPTA) showed increase in viscosity but decrease when hexanediol diacrylate or 1,6-hexadiol diacrylate (HDDA) was used.The dynamic mechanical thermal properties of EFBIPP composites showed that the storage modulus (E') decreases with increase in temperature. The E' also increases with increase in the fibre loading in the composite. However the E' was not affected by the fibre size. The EFBIPP composite showed the glass transition temperature (T,) of the composite was shifted to lower temperatures than the T, of the pure PP. The MAPP treatment resulted in a remarkable increase in E' and loss modulus (E"). However the damping property (tan 6) is less affected. Type of MAPP showed significant different with MAPP 'A' gives a better performance of E' compare than MAPP 'B'. The E' and E" increased with the addition of reactive additives compared to those without RA and the T, reduces to low temperature as compared to the irradiated EFBIPP without RA. The tan 6 for the irradiated EFBIPP with RAs also changed with the percentage of RA concentrations